International risk of yellow fever spread from the ongoing outbreak in Brazil, December 2016 to May 2017 - Dorigatti,I; Hamlet,A; Aguas,R; Cattarino,L; Cori,A; Donnelly,CA; Garske,T; Imai,N; Ferguson,NM (EUROSURVEILLANCE, 2017)
States in south-eastern Brazil were recently affected by the largest Yellow Fever (YF) outbreak seen in a decade in Latin America. Here we provide a quantitative assessment of the risk of travel-related international spread of YF indicating that the United States, Argentina, Uruguay, Spain, Italy and Germany may have received at least one travel-related YF case capable of seeding local transmission. Mitigating the risk of imported YF cases seeding local transmission requires heightened surveillance globally.